The Role of Hemocytes in the Hawaiian Bobtail Squid, Euprymna scolopes: A Model Organism for Studying Beneficial Host–Microbe Interactions - McAnulty, Sarah J.; Nyholm, Spencer V. (Frontiers in Microbiology, 2017)
Most, if not all, animals engage in associations with bacterial symbionts. Understanding the mechanisms by which host immune systems and beneficial bacteria communicate is a fundamental question in the fields of immunology and symbiosis. The Hawaiian bobtail squid (Euprymna scolopes) engages in two known symbioses; a binary relationship with the light organ symbiont Vibrio fischeri, and a bacterial consortium within a specialized organ of the female reproductive system, the accessory nidamental gland (ANG). E. scolopes has a well-developed circulatory system that allows immune cells (hemocytes) to migrate into tissues, including the light organ and ANG. In the association with V. fischeri, hemocytes are thought to have a number of roles in the management of symbiosis, including the recognition of non-symbiotic bacteria and the contribution of chitin as a nutrient source for V. fischeri. Hemocytes are hypothesized to recognize bacteria through interactions between pattern recognition receptors (PRRs) and microbe-associated molecular patterns (MAMPs). Colonization by V. fischeri has been shown to affect the bacteria-binding behavior, gene expression, and proteome of hemocytes, indicating that the symbiont can modulate host immune function. In the ANG, hemocytes have also been observed interacting with the residing bacterial community. As a model host, E. scolopes offers a unique opportunity to study how the innate immune system interacts with both a binary and consortial symbiosis. This perspective will recapitulate what is known about the role of hemocytes in the light organ association and offer future directions for understanding how these immune cells interact with multiple types of symbioses.